2007
DOI: 10.1002/cphc.200700081
|View full text |Cite
|
Sign up to set email alerts
|

Spectroelectrochemistry of Carbon Nanostructures

Abstract: This review is focused on charge-transfer reactions at carbon nanotubes and fullerenes. The spectroelectrochemistry of fullerenes deals with the spin states of fullerenes, the role of mono-anions and the reactivity of higher charged states in C60. The optical (Vis-NIR) spectroelectrochemistry of single-walled carbon nanotubes (SWNTs) follows changes in the allowed optical transitions among the Van Hove singularities. The Raman spectroelectrochemistry of SWNT benefits from strong resonance enhancement of the Ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
240
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(251 citation statements)
references
References 213 publications
(539 reference statements)
11
240
0
Order By: Relevance
“…A characteristic Raman spectrum of the SWCNTs (Fig. 3, red line) shows mainly four bands: the radial breathing mode (RBM), the disorder induced mode (D), the tangential displacement mode (G) and the high frequency two phonon mode (G') [47][48][49][50][51][52]. These bands are completely similar before and after preparation of the film.…”
Section: Preparation Of Free-standing Swcnt Electrodesmentioning
confidence: 90%
See 1 more Smart Citation
“…A characteristic Raman spectrum of the SWCNTs (Fig. 3, red line) shows mainly four bands: the radial breathing mode (RBM), the disorder induced mode (D), the tangential displacement mode (G) and the high frequency two phonon mode (G') [47][48][49][50][51][52]. These bands are completely similar before and after preparation of the film.…”
Section: Preparation Of Free-standing Swcnt Electrodesmentioning
confidence: 90%
“…Spectroscopic characterization was performed by Raman spectroscopy, due to the valuable information on the vibrational properties of nanotubes that this technique provides [47][48][49][50][51]. It allows us to verify that the integrity of the SWCNTs is not affected during the electrode fabrication.…”
Section: Preparation Of Free-standing Swcnt Electrodesmentioning
confidence: 99%
“…6,7 These pioneering investigations have unambiguously demonstrated that SWNTs give rise to reversible capacities outperforming those theoretically predicted for graphite, that is, 460 versus 372 mAh/g, which is equivalent to a Li 1.23 C 6 stoichiometry. A setback is that initially a large irreversible capacity of 1200 mAh/g evolved.…”
Section: Sgobba and Guldi (Continued From Previous Page)mentioning
confidence: 98%
“…11 On the other hand, a finer tuning of the added charge in the SWNTs can be accomplished electrochemically by varying the potential at their contact interface with an electrolyte solution. 3,12,13 In this case, the electrolyte ions do not readily penetrate the SWNT ropes. Instead, during the initial stages of electrochemical doping in potentiostatic mode, they form a charged double layer only with the external surface of the ropes.…”
Section: Introductionmentioning
confidence: 99%
“…Instead, during the initial stages of electrochemical doping in potentiostatic mode, they form a charged double layer only with the external surface of the ropes. 3,[12][13][14][15] This is of key importance for SWNT applications as actuators, because SWNT expansion or contraction can be related to the transferred charge, which in the double-layer model can be calculated from the applied voltage. 12,13 On the other hand, intercalation can also be performed electrochemically when galvanostatic mode is applied.…”
Section: Introductionmentioning
confidence: 99%